Svjaz' kinematiceskich charakteristik prizemlenija i effektivnosti uderžanija vertikal'noj pozy u gimnastov 8-9 let - Botova, L. N.; Derevyanko, O. I. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
In this article, we consider the kinematic characteristics of the landing after the vertical fall on the support without rotation (deep jump), performed by the gymnasts aged 8-9, as well as stabilometric test indicators. The study involved gymnasts aged 8-9, with training experience of 3.8±0.34 years, without pathologies of the lower extremities, including flat feet. The group consisted from 20 people. The main research methods included the stabilometric testing and video analysis of the movements (shooting frequency 100 shots / sec). We have received and processed the video materials in the "Simi Motion 9.0.1" software environment. The study has revealed that the lack of proper compensation of the shock load by the knee joints and trunk movement is the sequence of internal rotation of the knees. Asymmetric bending of the knees at the landing moment results in a greater inward displacement of the knees. Correlation was found between the effectiveness of development of the individual motor strategy for holding the fixed vertical posture and kinematic characteristics when performing the simple landing by gymnasts aged 8-9, which reflects high stabilometric indicators under optimal kinematic landing indicators.